2019
DOI: 10.1111/aas.13462
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for shivering during caesarean section under spinal anaesthesia. A prospective observational study

Abstract: Background Shivering during caesarean section (CS) under spinal anaesthesia is a common phenomenon. It could not only alter patient's physiology by increasing oxygen consumption but also affect the parturient's experience of childbirth. Shivering is thought to be associated with intraoperative hypothermia, but the risk factors and exact mechanism remain unclear. Methods We conducted a prospective, observational study to examine the potential risk factors for intraoperative shivering, including anxiety levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Besides, in different studies, patients have not been assessed by equal accuracy, especially lower grades of shivering (0 and 1) might not be detected. Furthermore, it has been shown that level of preoperative anxiety in pregnant women is strongly correlated with the severity of shivering (31). In this study, the incidence of perioperative DAR like, nausea, vomiting, hallucination, nystagmus, and sedation showed a significant difference among the four study groups.…”
Section: Discussionmentioning
confidence: 56%
“…Besides, in different studies, patients have not been assessed by equal accuracy, especially lower grades of shivering (0 and 1) might not be detected. Furthermore, it has been shown that level of preoperative anxiety in pregnant women is strongly correlated with the severity of shivering (31). In this study, the incidence of perioperative DAR like, nausea, vomiting, hallucination, nystagmus, and sedation showed a significant difference among the four study groups.…”
Section: Discussionmentioning
confidence: 56%
“…Traditionally, shivering is largely attributed to intra-operative hypothermia, but shivering could have multiple causes in the parturient and the mechanisms remain unclear. 25 Feng and colleagues 26…”
Section: Resultsmentioning
confidence: 99%
“…Anxiety and stress can have adverse impacts on pregnant women and the fetus, as well as on postoperative recovery and the length of hospital stay [ 22 , 23 ]. A previous study reported that anxiety could contribute to shivering during cesarean sections [ 15 ]. Our present study further confirmed this result.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying and minimizing the risk factors associated with intraoperative shivering could reduce the incidence of shivering and improve maternal outcomes. Several previous studies have suggested that anxiety, hypotension, and hypothermia may be associated with intraoperative shivering during cesarean sections [ 3 , 15 ], but another study failed to demonstrate a relationship between anxiety and shivering during surgical operations [ 16 ]. Studies have also suggested that epidural anesthesia might affect shivering, but the results are controversial [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%